A functorial approach to the behaviour of multidimensional control systems - Pommaret, Jean-François; Quadrat, Alban (Zielona Góra: Uniwersytet Zielonogórski)
We show how to use the extension and torsion functors in order to compute the torsion submodule of a differential module associated with a multidimensional control system. In particular, we show that the concept of the weak primeness of matrices corresponds to the torsion-freeness of a certain module.
Keywords: multidimensional systems; weak primeness; controllability; algebraic analysis; torsion and extension functors; rings of differential operators